Climate Change Adaptation and Disaster Risk reduction integration: Strategies, Policies, and Plans in three Australian Local Governments. (September 2017) - Forino, Giuseppe; von Meding, Jason; Brewer, Graham; van Niekerk, Dewald
Abstract: Climate Change Adaptation (CCA) and Disaster Risk Reduction (DRR) integration is a pressing concern for Australia. Normative instruments such as Strategies, Policies, and Plans are among the principal ways that Local Governments (LGs) use to promote CCA&DRR integration. To understand how CCA&DRR integration is promoted into Strategies, Policies, and Plans by Australian LGs, the paper performs a content analysis of documents in Singleton, Newcastle, and Lake Macquarie - three LGs located in the Hunter region, New South Wales (NSW). Findings indicate that: (i) the three selected LGs recognize that climate change exacerbates frequency and intensity for hazards; (ii) some documents include common goals for promoting CCA, showing synergies among different topics; (iii) documents recommend CCA measures for several aspects of the built environment, including land-use, building standards, and infrastructure and asset materials; and, (iv) public participation mechanisms were proposed to enact CCA measures. While these measures are important, understanding how CCA will be implemented is still necessary. Fragmentation exists between CCA goals in these LGs and future programs by the NSW government for the built environment in the Hunter region. Additionally, efforts are required to understand how public participation mechanisms can contribute to addressing vulnerabilities to climate change-related hazards. Finally, the initial evidence shows that the Lake Macquarie LG shows greater commitment in CCA&DRR integration than Newcastle and Singleton LGs. The paper demonstrates that a focus on how LGs promote CCA&DRR integration into Strategies, Policies, and Plans can extend our understanding of climate change response by LGs.